Short report: Application of an alternative Aedes species (Diptera : Culicidae) surveillance method in Botucatu City, São Paulo, Brazil - Nogueira, L. A.; Gushi, L. T.; Miranda, J. E.; Madeira, N. G.; Ribolla, PEM (Amer Soc Trop Med & Hygiene, 2005)
One of the main problems with dengue is the control of Aedes aegypti, its major vector. In Brazil, the current control program for Ae. aegypti and Aedes albopictus populations includes larval density surveys. An interesting alternative is the use of a distinct index, the Premise Condition Index (PCI). This tool relates conditions of property, such as houses and yards, and the degree of shade with the occurrence of Aedes sp. oviposition, and is calculated as scores from 3 to 9. The lowest score indicates property in good condition and an unfavorable breeding environment, while the highest score indicates property at high risk for infestation by Aedes sp. The present study is based on the application of the PCI in an urban area of Botucatu, Brazil to confirm its effectiveness.